Teor crítico de cloretos para o aço galvanizado em matrizes de concreto com distintas composições e alcalinidades - Bezerra, Wesley Vítor Dantas de Carvalho (2022)
In reinforced concrete structures located near environments with high concentrations of chloride ions (e.g., marine environment), the reinforcement is susceptible to the occurrence of localized corrosion. The critical chloride threshold is the minimum amount of chlorides necessary to depassivate these reinforcements. Although there are already several publications on the critical chloride threshold, the literature still lacks data on this threshold for galvanized steel. Samples of different types of concrete (varying the type of cement – high initial strength, pozzolanic and with ground granulated blast furnace slag) reinforced with different types of steel (galvanized with different immersion times in zinc bath and CA-50 carbon steel) were subjected to immersion and drying cycles in aqueous sodium chloride solution (3.5% Cl- by mass). From the open circuit potential and linear polarization resistance, the depassivation was identified in each bar. It was noticed that the galvanized steel presents greater resistance to the chloride environment in comparison with the carbon steel. However, the use of matrices with high alkalinity can compromise their performance. In this study, galvanized bars performed worse than carbon steel when embedded in high initial strength concrete (pH = 13.01). Replacing 15% of the reference cement (VARI RS) with metakaolin more than doubled the time required for corrosion initiation, regardless of steel type. This fact is due to the high chloride binding capacity of metakaolin. Finally, for the titrations, the galvanized bars with the longest immersion time in the zinc bath (GS6) were selected. The critical threshold of free and total chlorides of GS6 were 0.76% and 1.37% for concrete with granulated blast furnace slag (III) and 0.74% and 1.19% for concrete of high initial strength (V), respectively, being these percentages in relation to the binder mass. GS6 bars embedded in pozzolanic concrete (IV) are still passive, even after 283 days of exposure.